Environmental enrichment increases the number of telencephalic but not tectal cells of angelfish (Pterophyllum scalare): an exploratory investigation using optical fractionator - Diniz, Daniel Guerreiro (Springer, 2020)
Based on previous evidence that environmental enrichment is associated with telencephalic cellular proliferation and that stable visuotopic tectal circuits are essential for discrimination of placement and identity of stationary or moving objects in the visual field, differential plasticity is expected in these areas. Here we tested this hypothesis in the Angelfish (Pterophyllum scalare), a species of ornamental fish with great value in the aquarist trade. We hypothesized that total telencephalic cell number would increase under the influence of an enriched environment whereas the tectal cell number would not change. To test this hypothesis, 12 aquaria of 80 l each were used, with six fish in each. The aquaria had either an enriched environment (EE) including stones, plants, sand and the presence of another fish from the Loricariidae family for interspecific social interaction, or an impoverished environment (IE), in which stimuli were limited to intraspecific interactions in a barren aquarium. After 62 days, six fish from each treatment were euthanized, and their brains were fixed and sectioned for Nissl staining. Then, stereological estimates of the total number of cells were performed. The fish showed no differences in weight gain, feed conversion ratio, condition factor, specific growth rate or survival. Animals kept in the enriched environment had a higher number of total telencephalic cells than animals kept in the impoverished environment (1,038,555 ? 65,357 vs. 758,331 ? 51,587, bilateral t-test, p = 0.008), but a similar number of tectal optical cells (EE 424,097 ? 29,914 vs. IE 471,409 ? 50,850, bilateral t-test, p = 0.445752). We concluded that cell proliferation in response to stimulation by the enriched environment is differentially expressed in the telencephalon and tectal areas of Pterophyllum scalare.